A saúde e seu direito sob o olhar do usuário - Pacheco Filho, Antônio Carlos[UNESP]; Garbin, Cléa Adas Saliba [UNESP] (My University, 2010)
Introduction: The health on its large conception and not only like a sicken process, is an indispensable benefit to the human life. The valid Brazilian Constitution has a session destined just for the health, a conquest for society. Objective: The aim of this research was to know the perception of Single Health System users about health e their rights in this field. Methodology: Descriptive research with qualitative approach. The data collect was realized by interviews, using a script, specially elaborated for this study, contemplating questions referent to the theme. The qualitative analysis was chosen because this analysis type is sensible to understand the answers obtained through interviews with the research subjects from a Primary Care Unit. Results: The subjects have a fragmented vision about health, in the other words, with a focus in assistance and cure. Health was identified by them only in relation with health services and sick process. Many users are unaware that health is a right of every citizen in Brazil. Conclusion: The health rights in Brazil were given to society and should be closer to the population.

Introdução: A saúde, em sua concepção ampliada e não apenas como um processo de adoecimento, é um bem indispensável à vida do ser humano. A Constituição vigente possui uma seção destinada somente a ela, uma conquista para a sociedade. Objetivo: Conhecer a percepção sobre o conceito saúde e o direito à saúde de usuários do Sistema Único de Saúde. Metodologia: A pesquisa é descritiva com abordagem qualitativa. A coleta dos dados foi realizada por meio de entrevistas, utilizando um roteiro especialmente elaborado para o estudo, contemplando questões referentes ao tema. A análise qualitativa foi a eleita por cuidar com preciosismo das falas transcritas. Os sujeitos da pesquisa foram usuários de uma Unidade Básica de Saúde. Resultados: A visão da saúde, por parte dos usuários, está fragmentada, ou seja, há um enfoque assistencialista e curativista, em que a saúde foi identificada com os serviços de saúde e processos de adoecimento. Muitos usuários não sabem que a saúde é um direito de todo cidadão. Conclusão: Os direitos são postos à sociedade para serem sentidos e não para ficar a uma distância em que não seja possível a sociedade ao menos reconhecê-los.
The health and its right in the user’s view
Keywords: Right to health; Single health system; Constitution; Direito à saúde; Sistema Único de Saúde; Constituição